Determinants of bank failures in a deregulated context : evidence from the Portuguese banking sector in the 19th century - Silva, Ana Carolina Carreira Rebelo (2019)
This dissertation investigates the determinants of bank failures in the absence of comprehensive regulatory policies and of supervision in the banking sector. These features trigger the incorporation of new banks, contributing to an increasingly competitive environment. The fintech landscape still lacks regulation and it is increasingly composed by more players, which are gaining a foothold in the banking sector by offering more sophisticated and customized products and services than conventional banks. Since this new fintech era shares those peculiarities with the 19th century Portuguese banking sector, the latter was considered as an ideal and “clean” laboratory to study bank failures. This prevents the emergence of potential puzzling effects given that the banking sector in Portugal was relatively new and simple. In this sense, it was built a new dataset comprising the Portuguese banks’ accounts between 1858 and 1887 to evaluate the bankruptcies and survivals of banks after the 1876 crisis. This thesis shows that the age of a bank is critical to survive a crisis following a period of deregulation which led to the increase of the number of banks operating. Further analysis indicates that having a low level of capital and providing unbalanced amounts of credit, significantly higher than deposits, are also determinant to bank failures.